Effect of Heat Loss on the Working Index of Electric Arc Furnace (EAF) - Okediran, Iliyasu; Adetunji, Olayide; Adeboye, Busayo; Adefajo, Abdulhafiz (Universitas Muhammadiyah Magelang, 2023)
Day in day out of human life the use of metal is inevitable, metals are needed for different purposes such as in construction of bridges houses, roads etc. but despite the availability of huge amount of metal, it does not meet the global demand thus this paper investigate the effect of reduction of power of heat loss on the cost of production of electric arc furnace. In order to achieve maximum precision during production, getting product at relatively reduced price has remained a major challenge to the scientists. The experiment was conducted at industrial scale whereby power of heat loss was varied from 7.707- 4.624 MW while energy consumption fell from 0.5463 to 0.5317 MW-Hour per ton and productivity q tremendously increased from 253.0 ton to 254.0 ton per hour . Data used were collected from active furnace in Zerepaves Metallurgical plant, Russia and further analyzed with software package for accuracy